Hop Volatile Compounds (Part II): Transfer Rates of Hop Compounds from Hop Pellets to Wort and Beer - Hanke, Stefan; Herrmann, Markus; Rückerl, Johannes; Schönberger, Christina; Back, Werner (BrewingScience, 2008)
Several hundred aroma compounds are known in hops but only a few have great impact to hop aroma of beer. Adding hops at late stages of boiling gives a pleasant hoppy flavour to the final beer. Linalool is known to be a good indicator for such a hoppy flavour. In this study it could be shown that different hop varieties have different transfer rates of linalool and other aroma compounds. The behaviour of the aroma compounds is different and compound specific. Linalool increases during fermentation and there were differences between beers fermented at 8 °C and 12 °C. The 12 °C samples showed lower concentrations of linalool but higher scores in aroma intensity. Possible explanation are additive interactions between fermentation-by-products and hop aroma compounds.